2021
DOI: 10.1108/ijchm-05-2021-0559
|View full text |Cite
|
Sign up to set email alerts
|

Contactless service in hospitality: bridging customer equity, experience, delight, satisfaction, and trust

Abstract: Purpose Draws from the equity theory and customer equity literature, this study aims to argue that the implementation of contactless service as an innovative service design in the hospitality industry can generate customers’ emotional attachment and cognitive evaluation of the brand. Design/methodology/approach This study uses partial least squares modeling and data from a large-scale survey of hotel guests who have experienced contactless service in mainland China. The authors performed an importance-perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 84 publications
(138 reference statements)
5
68
0
1
Order By: Relevance
“…dining environment, communication and hygiene and contactless features). Consistent with the findings of this study, Hao and Chon (2021) argued that implementing contactless features in the hospitality industry during the pandemic helped build a trustful relationship between customers and companies. And finally, to develop a holistic conceptual framework, this study incorporated two COVID-19-focused measurement items, perceived risk and support of the restaurant, to identify their moderating roles in the relationships among the five proposed measurement items (i.e.…”
Section: Theoretical Implicationssupporting
confidence: 86%
See 2 more Smart Citations
“…dining environment, communication and hygiene and contactless features). Consistent with the findings of this study, Hao and Chon (2021) argued that implementing contactless features in the hospitality industry during the pandemic helped build a trustful relationship between customers and companies. And finally, to develop a holistic conceptual framework, this study incorporated two COVID-19-focused measurement items, perceived risk and support of the restaurant, to identify their moderating roles in the relationships among the five proposed measurement items (i.e.…”
Section: Theoretical Implicationssupporting
confidence: 86%
“…Given that people are more likely to avoid direct contact in a service environment, the importance of the contactless feature in restaurants is increasing. Even before COVID-19, technology-based IJCHM 34,2 contactless functions have been widely used in many aspects of the restaurant industry, including operational and strategic management (Hao and Chon, 2021). Cavusoglu (2019) found that mobile payment, online ordering, barcode scanners and take-out/delivery systems were much less used compared to traditional front-of-house technology, such as a point-of-sale system.…”
Section: Contactless Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This research also attempted to measure the stress-recovery dimension of lodging experience, although other dimensions are mostly related to servicescape or customer interaction (Hao and Chon, 2021;Pelet et al, 2021). This may explain why lodging recovery experiences explained simply 8% of the variance with guest satisfaction, which is considered a limitation of the study.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Second, a latent, single factor was added to the proposed model to calculate the most shared variance (i.e., covariance) explained by this single factor. Based on Hao and Chon’s (2021) study, the most shared variance explained by one factor should be less than 50%. Results show that this specific value for the current study is 29.38%, indicating a low risk of CMB ( Hao and Chon, 2021 ).…”
Section: Resultsmentioning
confidence: 99%